Pengaruh Pemutihan Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening - Shella Karnova; Bambang Supeno; Agus Seswandi (JURNAL ECONOMINA, 2024)
Regional development includes the ability to effectively monitor local economic resources, which in turn generates income for the region and contributes to governance and regional growth that provides benefits to society. In order to increase regional income and facilitate regional growth, all taxpayers are asked to carry out their tax obligations based on the tax law established by the regional government. This is caused by various things, including reducing vehicle taxes, taxpayer compliance and taxpayer awareness. The aim of this research is to analyze the effect of tax whitening on motor vehicle taxpayer awareness, tax whitening on taxpayer compliance, taxpayer awareness of tax compliance, tax whitening through taxpayer awareness of taxpayer compliance. The research method is quantitative with descriptive explanations, this research uses a sample of 245 and data processing uses SEM PLS. Research findings show that 1) Tax whitening has a positive effect on motor vehicle taxpayer awareness 2) Tax whitening has a positive effect on taxpayer compliance 3) Taxpayer awareness has a positive effect on taxpayer compliance 4) Tax whitening through taxpayer awareness has an effect on taxpayer compliance at the Selat Panjang Samsat.